Delayed gastric emptying is not associated with a microbiological diagnosis of small intestinal bacterial overgrowth - Calderon, Gerardo (Dig Dis Sci, 2020)
BACKGROUND: Clinical symptoms of patients with small intestinal bacterial overgrowth (SIBO) may overlap with symptoms of gastroparesis. Prior studies suggest delayed small intestinal transit is associated with SIBO, but have not shown an association between delayed gastric emptying and SIBO. However, these studies have generally relied on the indirect method of breath testing to diagnose SIBO. AIMS: The aim of this study was to examine the association between a microbiological diagnosis of SIBO and delayed gastric emptying by scintigraphy. METHODS: In a single-center retrospective study of previous research participants who presented for small bowel enteroscopy for diagnostic evaluation of SIBO, we identified 73 participants who underwent gastric emptying study by scintigraphy. A microbiological diagnosis of SIBO was made in patients based on culture results of jejunal aspirates. Clinical symptoms were assessed using the total gastroparesis cardinal symptom index (GCSI) score. We compared delayed gastric emptying, 2- and 4-hour gastric retention, and gastroparesis symptoms between patients with and without a microbiological diagnosis of SIBO. KEY RESULTS: Among 29 participants with SIBO and 44 without SIBO, 33 (45%) had evidence of delayed gastric emptying. There was no significant association between a microbiological diagnosis of SIBO and delayed gastric emptying by scintigraphy. Percent retained at 2 and 4 hours and total GCSI scores did not differ significantly between those with and without SIBO. CONCLUSIONS: Although delayed gastric emptying is common in patients with suspected SIBO, gastric emptying is not associated with a microbiological diagnosis of SIBO.